2D image reconstruction of radar INDERA - Sediono, Wahju; Lestari, Andrian Andaya (Institute of Electrical and Electronics Engineers ( IEEE ), 2011)
INDERA is the first Indonesian maritime radar that works using the frequency modulated continuous wave (FMCW) technology. In the surveillance mode INDERA continuously transmits modulated electromagnetic waves to detect targets in the surrounding area. Since the transmitted signal is a continuous wave, INDERA needs only a very small power to transmit its signal. Consequently, the level of signals arrived on the Rxantenna part is also very low. The frequency of the transmitted signal is varied with time. As a result, the signal reflected by a target will generate a beat signal with a frequency proportional to the target distance. Thus basically we can compose a twodimensional image from such signals. In this paper we present a method to reconstruct a 2D radar image from the signals received by radar INDERA.